AN INVESTIGATION INTO FIRM PERFORMANCE DURING THE COVID-19 PANDEMIC IN THE BALTIC STATES - Derick Blaauw; Anmar Pretorius (Baltic Journal of Economic Studies, 2025)
The COVID-19 pandemic disrupted economic activity globally. Local restriction as well as restrictions imposed by trading partners led to job losses and firms in certain industries being affected disproportionally. The three Baltic states were affected slightly later than their bigger counterparts. Against this background, the study analyzed factors pertaining to firm performance in Estonia, Latvia and Lithuania during COVID-19 based on enterprise survey data from the World Bank. Cross sectional regressions are estimated to identify factors that potentially could help determine why firms in certain industries and certain countries were more prone to job losses than others. Classic microeconomic factors, e.g., changes in sales, played a critical role in the performance of the firms during the pandemic – specifically relating to the number of full-time employees. Bigger firms were more likely to preserve jobs, as well as firms that adjusted salaries and other benefits received by employees. Firms in a better position to function on-line also preserved more jobs. The disaggregation of the country samples into different industries provides evidence that industry composition and other context-specific factors play a key role in explaining firm performance at industry/sector level. Various interactive dummy specifications to cater for the gender dimension, local ownership and export involvement yielded heterogeneous results. From a macro perspective, Lithuania’s economic climate during a growth phase provided more support to firms as well as government support in terms of wage subsidies. position the business cycle the general. Even though pandemics of this nature do not occur regularly, specific factors found to be statistically significant in the empirical study could provide guidelines on how to preserve job opportunities during periods of global downturn in general.